Carolingian Renaissance: Schools and Features of Education - Stančienė, Dalia Marija; Žilionis, Juozas (Acta Paedagogica Vilnensia, 2006)
In the history of European culture the Carolingian Renaissance is a very special period of consolidation and transformation of an ancient cultural and educational heritage, which took root in the lands of the Franks ruled by Charlemagne. Such remarkable scholars and teachers as Benedict Biscop, the Venerable Bede and Alcuin worked during that period. They opened schools, established libraries and other cultural institutions. Alcuin supervised the Carolingian reform of education and wrote didactic textbooks in which, along with the presentation of the subject-matter, he discussed the purposes, motives and methods of learning. The schoolwork, presented in the textbooks, was closely connected with the cultural facts, which had to be known by each well-educated citizen of the Carolingian Empire. The education was based on the Seven Liberal Arts program and Socratic Method of teaching, which had to inspire disciples for dialogue as well as the individual search for truth, for self-learning and teaching.